Training, Work Experience and Motivation on the Performance of the Regional Revenue Agency Office of Labuhanbatu Regency - Candra Kirana; Zulkifli Musannip Efendi Siregar; Abd. Halim (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2022)
This study aims to analyze Training, Work Experience and Motivation on the Performance of Employees of the Regional Revenue Agency Office of Labuhanbatu Regency.This type of research is quantitative, and the place of this research is the Regional Revenue Agency Office of Labuhan Batu Regency. Data collection techniques used in the study were observation, documentation and questionnaires using a Likert scale. The population in this study were employees of the Regional Revenue Agency of Labuhan Batu Regency as many as 90 people. The sampling technique used is saturated sampling. Saturated sampling technique is a sampling technique when all members of the population are used as samples, thus all employees are used as respondents in this study. The analytical method used in this research is validity and reliability test, classical assumption test which includes: data normality test, heteroscedasticity test, and multicollinearity test. Multiple linear regression analysis was tested using partial (t), simultaneous (F) testing, and the coefficient of determination. The test results partially prove that the value of t count is 3.809 > t table 1.6629 which indicates thattraining (X1) has a positive effect on employee performance variables (Y). The t-count value is 2.629 > t table 1.6629 explaining that experience (X2) has a positive effect on employee performance variable (Y). Furthermore, the value of t count is 4.087 > t table 1.6629 which means that motivation (X3) has a positive effect on employee performance variable (Y). Simultaneous test results obtained Fcount value of 61.537> Ftable 2.48 with a significance value of 0.000 <0.05. The results of this F test explain that training (X1), work experience (X2), and motivation (X3) simultaneously have a positive and significant effect on employee performance (Y). The value of R Square from the analysis of the coefficient of determination is 0.682, which means that employee performance (Y) can be explained by the training variable (X1), work experience (X2).